2011
DOI: 10.1614/wt-d-11-00027.1
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide Programs for Enhanced Glyphosate-Resistant and Glufosinate-Resistant Cotton (Gossypium hirsutum)

Abstract: Research was conducted at experimental research stations near Keiser and Marianna (Marianna-A), AR, in 2007, and in a grower's field near Marianna (Marianna-B), AR, in 2008, to compare herbicide programs, including POST application(s) of glyphosate/glufosinate alone or in combination with residual herbicides applied as PRE, mid-POST (MPOST), or layby POST-directed (PD) in enhanced glyphosate- and glufosinate-resistant cotton. Weed species evaluated included Palmer amaranth, pitted morningglory, hemp sesbania, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 26 publications
1
20
0
1
Order By: Relevance
“…Eubank et al (2012) also observed this synergistic effect with the addition of metribuzin to paraquat on control of glyphosate-resistant horseweed [ Conyza canadensis (L.) Cronq.]. It is well established that contact herbicides are less effective than glyphosate in controlling grasses (Riar et al 2011; Whitaker et al 2011). Although significantly less fresh biomass weight was observed in the glufosinate-treated plots compared with the nontreated check, dry biomass weights did not show such differences among treatments on both cover crops (Table 8).…”
Section: Resultsmentioning
confidence: 97%
“…Eubank et al (2012) also observed this synergistic effect with the addition of metribuzin to paraquat on control of glyphosate-resistant horseweed [ Conyza canadensis (L.) Cronq.]. It is well established that contact herbicides are less effective than glyphosate in controlling grasses (Riar et al 2011; Whitaker et al 2011). Although significantly less fresh biomass weight was observed in the glufosinate-treated plots compared with the nontreated check, dry biomass weights did not show such differences among treatments on both cover crops (Table 8).…”
Section: Resultsmentioning
confidence: 97%
“…Residual herbicides are crucial for obtaining season-long control of glyphosate-resistant Palmer amaranth (Jha and Norsworthy 2009;Neve et al 2011). Improved early season control of glyphosate-resistant and glyphosate-susceptible weed species with PPI residual herbicides in RR and LL soybean and cotton has been widely reported (Culpepper et al 2000;Riar et al 2011a). The average cost of herbicides in RR soybean was US$78 ha À1 and in LL soybean was US$91 ha À1 in the midsouth collectively.…”
Section: Resultsmentioning
confidence: 99%
“…Fomesafen and glufosinate are used to control broadleaf weeds in major agronomic crops in the US and have become effective and widely used alternatives to glyphosate in these crops, especially when glyphosate-resistant weed biotypes are present [17][18][19][20][21][22]. There is concern that widespread and repeated use of these herbicides could lead to selection for resistance to the modes of action represented by fomesafen and glufosinate.…”
Section: Introductionmentioning
confidence: 99%